2005
DOI: 10.1007/s10142-005-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Wheat genome structure: translocations during the course of polyploidization

Abstract: The genomic organization of Triticum timopheevii (2n=28, AtAtGG) was compared with hexaploid wheat T. aestivum (2n=42, AABBDD) by comparative mapping using microsatellites derived from bread wheat. Genetic maps for the two crosses T. timopheevii var. timopheevii x T. timopheevii var. typica and T. timopheevii K-38555xT. militinae were constructed. On the first population, 121 loci were mapped, and on the second population 103 loci. The transferability of the wheat markers to T. timopheevii was generally better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 39 publications
2
31
0
3
Order By: Relevance
“…Fourteen out of 46 primer pairs (30%) mapped on the chromosomes of the D genome amplified fragments in T. timopheevii. Three of them (gwm608, gwm205, and gdm84) were located to the T. timopheevii chromosomes (4G, 5G, and 1G, respectively), the chromosomal localization of the others is unknown thus far (Salina et al 2006). The absence of amplification of microsatellite markers in T. aestivum − T. timopheevii introgression lines can be explained as substitutions or translocations, as well as by deletions in chromosomes of the T. aestivum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen out of 46 primer pairs (30%) mapped on the chromosomes of the D genome amplified fragments in T. timopheevii. Three of them (gwm608, gwm205, and gdm84) were located to the T. timopheevii chromosomes (4G, 5G, and 1G, respectively), the chromosomal localization of the others is unknown thus far (Salina et al 2006). The absence of amplification of microsatellite markers in T. aestivum − T. timopheevii introgression lines can be explained as substitutions or translocations, as well as by deletions in chromosomes of the T. aestivum.…”
Section: Resultsmentioning
confidence: 99%
“…Among different types of markers (RAPD, RFLP, SSR, ALFP, and SNP), SSR markers, or microsatellites, are the most informative for the analysis of hybrid forms because of higher polymorphism level, codominant inheritance, chromosome specificity and transferability between cultivated and wild species. Microsatellite markers have been effectively used in analysis of genetic diversity of cereals, construction of molecular-genetic maps, as well as for mapping of genes and quantitative trait loci (Plaschke et al 1995;Stachel et al 2000;Landjeva et al 2006;Salina et al 2006).…”
mentioning
confidence: 99%
“…, experiments with Genomic in situ Hybridization (GISH) and the construction of high-density molecular and genetic maps of common wheat and T. timopheevii showed that the emergence of polyploid wheats was accompanied by species-specifi c chromosomal rearrangements: translocation 4A-5A-7B with subsequent pericentric inversion in the chromosome 4A in Emmer group and 1G-4G-6A t +3A t -4A t in Timopheevi group (Jiang and Gill 1994 ;Liu et al 1992 ;Naranjo et al 1987 ;Rodríguez et al 2000 ;Salina et al 2006 ). Further analyses of intraspecifi c and interspecifi c diversity in various wheat species revealed differences between species as well as between geographic populations of the same species with respect to nuclear and cytoplasmic genome polymorphisms (Kilian et al 2007 ;Mori et al 2009 ;Salamini et al 2002 ), isozyme and storage protein spectra (Belay 2000 ;Nishikawa 1984 ), and C-banding patterns and chromosomal rearrangements (Badaeva et al 1994 ;Dedkova et al 2009 ;Kawahara 1997 ;Kawahara and Taketa 2000 ;Taketa and Kawahara 1996 ).…”
Section: Abstract C-banding • Chromosomes • Domestication • Evolutionmentioning
confidence: 99%
“…О тдаленная гибридизация между мягкой пшеницей (Triticum aestivum L.) и ее дикими сородичами широко используется в современных исследова-ниях для сравнительного изучения строения и эволюции геномов (Salina et al, 2006), а также с прикладной целью для извлечения полезных в селекции генов из генофонда диких видов, более приспособленных к изменяющимся условиям среды (Qi et al, 2007). Сравнительные физио-логические исследования у отдаленных генотипов дают большие возможности для выявления лимитирующих звеньев продукционного процесса.…”
unclassified